Educação bilingue em Moçambique e o empoderamento comunitário - Cumbane, Silvestre S. (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
In this article I explore the relationship between language, education and community. Based on the concepts of linguistic citizenship and funds of knowledge, I analyse education for citizenship in Mozambique, specifically the empowerment of communities and their knowledge in bilingual education as one of the impacts of the ideological and political orientations that govern the recent educational reform in Mozambique. Combining Linguistic Ethnography and Discourse Analysis, I discuss to what extent bilingual education in Mozambique allows communities to participate as active agents in education. This study is part of a lager ethnography research implemented in 5 rural primary schools of Matutuine and Manhiça Districts in Maputo province. The research involved 35 teachers, 5 school managers, 6 focus groups with parents and other community members and 2 representatives of ADPP-Mozambique. The study found that (i) communities have little participation and agency in the teaching and learning process, (ii) the school and its knowledge continue to be overvalued to the detriment of the communities and their knowledge